+0  
 
0
39
3
avatar

Using the definition of deriative (f(x+h)-f(x))/h could anyone show me how to calculate the deriative of 4/x^2? I know the answer is -8/x^3 but I don't know the steps to get there.

Guest Oct 29, 2017
Sort: 

3+0 Answers

 #1
avatar+90968 
+2

Using the definition of deriative (f(x+h)-f(x))/h could anyone show me how to calculate the deriative of 4/x^2? I know the answer is -8/x^3 but I don't know the steps to get there.

 

If you understand the diagram that goes with this, then it is easy to remember because it is totally logical.

 

Just replace the a with an x in this diagram and see if you can make sense of it.

 

 

\(f(x)=\frac{4}{x^2}\\ f(x+h)=\frac{4}{(x+h)^2}\\ \text{The gradient of the secant joining these points }\\ =\frac{rise }{run}\\ =\frac{f(x+h)-f(x)}{x+h-x}\\ =[f(x+h)-f(x)] \div h\\ =[\frac{4}{(x+h)^2}-\frac{4}{x^2}] \div h\\ =[\frac{4}{(x+h)^2}-\frac{4}{x^2}] \div h\\ =\frac{4x^2-4(x+h)^2}{hx^2(x+h)^2}\\ \)

 

\( =\frac{4x^2-4(x^2+2xh+h^2)}{hx^2(x^2+2xh+h^2)}\\ =\frac{-4(2xh+h^2)}{hx^2(x^2+2xh+h^2)}\\ =\frac{-4h(2x+h)}{hx^2(x^2+2xh+h^2)}\\\)

 

Now the gradient of the tangent will be the gradient ofthe secant as h tends ot 0

 

\(\text{gradient of tangent}\\ =\displaystyle\lim_{h\rightarrow 0}\;\;\frac{-4h(2x+h)}{hx^2(x^2+2xh+h^2)}\\ =\displaystyle\lim_{h\rightarrow 0}\;\;\frac{-4(2x+h)}{x^2(x^2+2xh+h^2)}\\ =\dfrac{-8x}{x^4}\\ =\dfrac{-8}{x^3}\)

Melody  Oct 29, 2017
 #2
avatar
+1

Thank you very much Melody!

Guest Oct 29, 2017
 #3
avatar+90968 
0

You are very welcome :)

Students, including me when I was young, find this all very mysterious and difficult to remember, but if you understand the diagram it is completely logical and not difficult to remember at all.   :)

Melody  Oct 29, 2017

20 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details